Integrated farming system for women empowerment in an island ecosystem - SWARNAM, T P; VELMURUGAN, A; PANDEY, S K; GEORGE, ZACHARIAH (The Indian Journal of Agricultural Sciences, 2025)
A study was conducted to assess the impact of integrated farming system on a smaller scale in tribal areas of Nicobar Island, India. A small scale Homestead Integrated Farming System (HIFS) comprising home garden, goat/pig, backyard poultry was evaluated in farmer’s field through participatory approach in three tribal villages of Car Nicobar during 2013–2020. To assess the impact of Integrated Farming System (IFS) on women empowerment, structured interview was carried out among 20 beneficiaries during October–November 2022. The women empowerment was assessed by quantitative and qualitative methods. Paired t test was conducted for different indicators of women economic and social empowerment comparing the baseline data collected before intervention in 2012. The study found an increase of average household income up to ₹15,000/- due to sale of surplus farm produce after home consumption from an area of 400 m2 in 2020–21. The system provided an opportunity for the tribal women to earn money on their own providing financial independence. The statistical analysis indicated a significant improvement in all the indicators of economic and social empowerment of women. The women economic empowerment index increased from 0.088 (nil empowerment) before to 0.437(slight empowerment) after intervention on Likert scale. This economic empowerment led to social empowerment, the index of which has increased from 0.097– 0.278 during the same period. The study indicated that a small scale homestead farming system can be a promising path in improved livelihoods, enhanced income for achieving economic and social empowerment of women in tribal, remote and isolated areas as in Nicobar Islands.